2013
DOI: 10.1158/1055-9965.epi-12-0435
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Cytokinesis-Blocked Micronucleus Assay to Detect Gender Differences and Genetic Instability in a Lung Cancer Case–Control Study

Abstract: Background: Although tobacco exposure is the predominant risk factor for lung cancer, other environmental agents are established lung carcinogens. Measuring the genotoxic effect of environmental exposures remains equivocal, as increases in morbidity and mortality may be attributed to coexposures such as smoking.Methods: We evaluated genetic instability and risk of lung cancer associated with exposure to environmental agents (e.g., exhaust) and smoking among 500 lung cancer cases and 500 controls using the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 90 publications
3
12
0
Order By: Relevance
“…We have previously reported in a pilot study and confirmed in a larger study (1820) that BN-MN and BN-NPB are strong predictors of lung cancer susceptibility with an overall positive predictive value of 96.1 and negative predictive value of 89.7 associated with disease status (19). In the current study, we externally validate our findings in an independent lung cancer population and test the effect of extending an existing lung cancer risk prediction model (21) with the CBMN endpoints.…”
Section: Introductionsupporting
confidence: 57%
“…We have previously reported in a pilot study and confirmed in a larger study (1820) that BN-MN and BN-NPB are strong predictors of lung cancer susceptibility with an overall positive predictive value of 96.1 and negative predictive value of 89.7 associated with disease status (19). In the current study, we externally validate our findings in an independent lung cancer population and test the effect of extending an existing lung cancer risk prediction model (21) with the CBMN endpoints.…”
Section: Introductionsupporting
confidence: 57%
“…In our study, we demonstrate that although both SCLC and NSCLC cases had significantly higher levels of genetic instability (BN-MN, BN-NPB, and BNBUDs) as compared to healthy cancer-free controls, only the levels of the BN-NPBs were significantly higher among the SCLC cases as compared to the NSCLC cases ( p < 0.001). While we have previously reported that the multi-endpoint CBMN assay is a sensitive predictor of lung cancer risk [McHugh et al, 2013], to our knowledge, this is the first study to compare the level of genetic instability between SCLC and NSCLC cases using this multiendpoint approach.…”
Section: Discussionmentioning
confidence: 99%
“…BN-BUDs represent a mechanism by which cells remove amplified DNA and are therefore considered a marker of possible gene amplification through a breakage-fusion-bridge cycle [Fenech, 2002a]. We have previously reported that the CBMN DNA damage endpoints are strong predictors of NSCLC susceptibility [El-Zein et al, 2006McHugh et al, 2013] with a positive predictive value of 91% among smokers.…”
mentioning
confidence: 99%
“…MN, NPBs, and NBUDs are nuclear alterations characteristic of chromosomally unstable cells often detected in tumor cells and peripheral blood of patients with cancer [41]. The frequency of nuclear alterations observed by CBMN is a relevant biomarker for the risk of lung cancer and melanoma, and can be used for early detection of the disease, making it a useful tool in clinical and epidemiological studies [42,43]. The CBMN method also allows assessment of the impact of micronutrients in the diet and the combination of micronutrients on DNA damage, revealing the carcinogenic or protective potential of certain diets [44,45].…”
Section: Introductionmentioning
confidence: 99%